A Sub-pixel detection algorithm of the MEMS dynamic fuzzy image - Yuan LUO; Chao JI; Yi Zhang; Zhangfang HU (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
The testing image have a certain degree of ambiguity when Application of machine vision method for MEMS dynamic parameters were measured.This paper presents a sub-pixel algorithm: Using self-similar characteristics of fractal interpolation to overcome the problem ,that can not be accurate interpolation and the edge of the image reconstruction. Then because of abilities of high resolution and anti-noise,after that using wavelet transform to obtain the image edge detection.The experimental results show that the algorithm can reach 0.02 pixel accuracy. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1643